Devastating delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage - Koopman, Inez; van Wijngaarden, Philippine B.; Rinkel, Gabriel J. E.; Vergouwen, Mervyn D. I. (Frontiers in Neurology, 2022)
Background We investigated the proportion of patients in an initial good clinical condition who developed devastating DCI, and aimed to characterize these patients by aneurysm location, blood pressure instability prior to DCI, and the extent of cerebral ischemia. Methods We included aSAH patients admitted between 2010 and 2021 with a Glasgow Coma Scale of 11 or higher 24 hours after aneurysm treatment, who developed devastating DCI, defined as DCI leading to coma for at least 48 hours with cerebral infarction on the subsequent scan. Blood pressure instability was defined as nimodipine-induced blood pressure drops, dosage adjustments, or the use of blood pressure drugs before onset of DCI. Descriptive statistics were used to summarize the data. Results Out of 1211 consecutive aSAH patients, 617 patients had a good clinical condition after aneurysm treatment of whom 16 (3%) patients (14 [88%] women) were included in this study. Thirteen (81%) patients had an aneurysm in the anterior circulation. Thirteen patients (81%) had blood pressure instability: twelve (75%) had nimodipine-induced blood pressure drops, eleven (69%) received antihypertensive drugs, and 7 (44%) received hypertension induction before onset of DCI. Thirteen (81%) patients had bilateral ischemia, mainly in the anterior circulation (56%). Conclusions The proportion of aSAH patients with a good clinical condition after aneurysm treatment who develop devastating DCI is small. The vast majority of these patients had blood pressure instability. Future studies are needed to investigate if a reduction in the number and extent of blood pressure fluctuations decreases the incidence of devastating DCI.